2017
DOI: 10.3847/1538-3881/aa6681
|View full text |Cite
|
Sign up to set email alerts
|

JVLA Observations of Young Brown Dwarfs

Abstract: We present sensitive 3.0 cm JVLA radio continuum observations of six regions of low-mass star formation that include twelve young brown dwarfs and four young brown dwarf candidates. We detect a total of 49 compact radio sources in the fields observed, of which 24 have no reported counterparts and are considered new detections. Twelve of the radio sources show variability in timescales of weeks to months, suggesting gyrosynchrotron emission produced in active magnetospheres. Only one of the target brown dwarfs,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 77 publications
2
13
0
Order By: Relevance
“…The proper motion direction is consistent with the orientation of the outburst nebula, the 12 CO blueshifted outflow (Feddersen et al 2020), and the position angle of the binary radio counterpart of HOPS 383 at 4 cm (Galván-Madrid et al 2015). We note that the unresolved 3 cm counterpart (Rodríguez et al 2017) corresponds to the faint northwest component at 4 cm, JVLA-NW, which suggests that JVLA-NW would be the base of the radio thermal jet launched by HOPS 383, whereas the brighter southeast component at 4 cm, JVLA-SE, would be an emission knot along this thermal jet (Fig. 1c).…”
Section: Near-infrared Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The proper motion direction is consistent with the orientation of the outburst nebula, the 12 CO blueshifted outflow (Feddersen et al 2020), and the position angle of the binary radio counterpart of HOPS 383 at 4 cm (Galván-Madrid et al 2015). We note that the unresolved 3 cm counterpart (Rodríguez et al 2017) corresponds to the faint northwest component at 4 cm, JVLA-NW, which suggests that JVLA-NW would be the base of the radio thermal jet launched by HOPS 383, whereas the brighter southeast component at 4 cm, JVLA-SE, would be an emission knot along this thermal jet (Fig. 1c).…”
Section: Near-infrared Resultssupporting
confidence: 88%
“…The blue pluses are radio sources (Galván-Madrid et al 2015;Rodríguez et al 2017). The blue and green arrows show the direction of the thermaljet candidate and the proper motion of the H 2 emission knot SMZ 1-2B, respectively.…”
Section: Observationsmentioning
confidence: 99%
“…The primary FU Tau A could be a low-mass star or a high-mass brown dwarf as its mass was estimated as ∼80 M Jup (Stelzer et al 2013). Multi-wavelength tracers ranging from X-ray, optical spectroscopy, to 3 cm free-free emission have indicated that FU Tau A is actively accreting and may also have outflows (Stelzer et al 2010(Stelzer et al , 2013Rodríguez et al 2017). The companion FU Tau b, 5.…”
Section: Targetsmentioning
confidence: 99%
“…The white contours show the 12 CO blueshifted outflow of HOPS 383 (Feddersen et al 2020). The blue pluses are radio sources (Galván-Madrid et al 2015;Rodríguez et al 2017). The blue and green arrows show the direction of the thermal-jet candidate and the proper motion of the H 2 emission knot SMZ 1-2B, respectively.…”
Section: Observationsmentioning
confidence: 99%